Development of adsorption air-conditioning technology using modified activated carbon – a review - T.H.C, Yeo; I.A.W, Tan; M.O, Abdullah (Elsevier Ltd, 2012)
Adsorption air-conditioning technology has attracted much attention recently due to its environmental friendly property. Some successes have been reported in the literature on the adsorption technology for air-conditioning applications. This paper presents an overview of the researches which had been carried out on adsorption refrigeration system with the commonly used adsorbent and adsorbate working pairs, solar adsorption refrigeration and adsorption technologies in automobile. Activated carbon has been widely used as the adsorbent in adsorption refrigeration system. However, one of the bottlenecks which prevent the improvement of the adsorption refrigeration technology using activated carbon is the use of the readily available commercial activated carbon without prior treatment, which has resulted in relatively lower performance as compared to the conventional absorption and vapour compression technologies. Various modification methods on activated carbon are thus discussed in this paper for future development and improvement of adsorption air-conditioning system.